Sixties Europe - Brown, Timothy Scott 1961- (New approaches to European history, 2020)
Sixties Europe examines the border-crossing uprisings of the 1960s in Europe on both sides of the Cold War divide. Placing European developments within a global context formed by Third World liberation struggles and Cold War geopolitics, Timothy Scott Brown highlights the importance of transnational exchanges across bloc boundaries. New Left ideas and cultural practices easily crossed bloc boundaries, but Brown demonstrates that the 1960s in Europe did not simply unfold according to a normative western model. Everywhere, innovations in the arts and popular culture synergized radical politics as advocates of workers' democracy emerged to pursue longstanding demands predating the Cold War divide. Tracing the development of a distinctive blend of cultural and political activism across diverse national settings, Sixties Europe examines an important, historically-recent attempt to address unresolved questions about human social organization that remain relevant in the present, and it offers an original history of Europe across a transformative decade